Tutoring in Teaching Art History – Effective Techniques and Strategies of Individualization on the Example of Teaching Medieval Art History - Krauze-Kołodziej, Aleksandra (Artifex Novus, 2024)
The article analyzes the effectiveness of selected elements of tutoring understood as various individualization strategies in teaching medieval art history. The basis of the article is a study involving an experimental component carried out as part of the Masters of Didactics (MoD) project organized by the Ministry of Education and Science (2017–2022). The teaching innovation consisted of introducing tutoring strategies into the curriculum of 2 subjects, including individualized exercises, creative and interactive approaches to learning, elective topics, and project scopes, clearly defined task criteria, individually given feedback, and personalized consultations. Before and after courses, a diagnostic and evaluation survey was conducted to assess students’ knowledge, expectations, and final opinions. Students’ opinions showed significant benefits, including increased understanding of the subject and gains in practical skills and soft skills. The article highlights the value of individualized teaching and learning in art history and its potential applications in other disciplines, contributing to the implementation of effective teaching strategies and increased student learning outcomes.